Biodiesel and diesel blends phytotoxicity in soil biodegradation - Bidoia, Ederio Dino [UNESP]; Tamada, Ivo Shodji [UNESP]; Lopes, Paulo Renato Matos [UNESP]; Cruz, Jaqueline Matos [UNESP]; Montagnolli, Renato Nallin [UNESP] (My University, 2015)
Oil spills cause substantial damage to the environment. Accidents in the petroleum industry create huge public concern, requiring effective responses from governments and corporations. There are also chronic impacts involving petroleum hydrocarbons, such as leaks in storage tanks, although they do not stand out as much in public opinion. Thus, continuous and prolonged pollution provides high environmental persistence of these compounds in soil, surface, and groundwater. The massive energy consumption based on non-renewable fossil fuels has led to the search for new sustainable and less polluting sources. Therefore, a viable alternative diesel fuel is biodiesel, originated from renewable sources, either plant or animal. Conventional physical soil treatment comprises of contaminants separation mostly, without any chemical degradation or transformation. These processes have many limitations and high cost. Most hydrocarbons are usually absorbed within the soil matrix by lowering its efficiency removal and absorption. Biological processes, in turn, are promising decontamination technologies, especially by combining simplicity and cost-effectiveness. Hence, bioremediation emerges as the least aggressive and best-suited eco-friendly technology, among the alternatives. Due to increasing use of biodiesel and bioremediation as a treatment tool, this study aimed to evaluate the phyto-toxicity in soil contaminated by diesel, biodiesel, and mixtures during different times of degradation. Seeds of Eruca sativa (arugula) and Lactuca sativa (lettuce) were used to observe inhibition of germination and seedling development, evaluated by germination index. Toxicity bioassays using biodiesel as a contaminant of animal or vegetable origin showed increased toxicity in all organisms tested over time of biodegradation in soil. The study showed that although biodiesel is a renewable energy source with great ecological appeal, some major precaution must be taken. Even withfavorable results for their higher biodegradability, other parameters must be considered to make biodiesel safe and ecologically viable by monitoring their toxicity.
Keywords: Bioremediation; Ecotoxicology; Germination; Hidrocarbon